Dejan Zavec - Zavec, Dejan (Šport (Ljubljana), 2014)
Dejan Zavec is the best Slovenian boxer. He became professional boxer in 2003.He competes in the welterweight category of up to 66.678 kg. In his professional career he has fought 36 duels of which he won 33 (18 by KO) and lost three. Throughout his career he has been awarded the titles of IBF World Champion, IBF, WBO and NBA Intercontinental Champion, European Union Champion and the International German Champion. The summit of his career, according to the IBF, was the victory in South-African Johannesburg on 11 December 2009. In his amateur career he won the Slovenian National Champion title ten times. His highest scores in the international boxing ratings included the fourth place in The Ring and the fifth place in BoxRec. Currently, he occupies the twelfth place in the IBF welterweight category ranking and the 34th place in the BoxRec ranking, among a total of 1692 fighters.
Keywords: boks; borilni športi; sport; šport; športniki; Zavec, Dejan, 1976-